Disaster Preparedness among Selected Beach Resorts in San Juan Batangas - Lacerna, Kristian C.; Dalugdog, Wilfredo D. (Future Science / FSH-PH Publications, 2025)
This study was conducted to assess disaster preparedness among selected beach resorts in San Juan, Batangas. A survey questionnaire was randomly distributed to 370 employees from the 10 most visited resorts in the area, and the collected data were analyzed using appropriate statistical tools. The results indicate that employees are consistently prepared across all aspects of disaster management, including prevention, response, recovery, and mitigation. A significant difference in disaster mitigation efforts was observed, suggesting that age influences how mitigation measures are understood and prioritized. The findings highlight a comprehensive preparedness approach among the resorts, emphasizing proactive prevention, efficient response protocols, effective recovery strategies, and robust mitigation efforts. This approach reflects a strong commitment to ensuring safety, resilience, and continuity of operations in the face of potential disasters. Despite the overall high level of preparedness, the study identified key areas for improvement, such as stockpile procurement, evacuation planning, psychosocial interventions, and structural resilience. Recommendations include conducting thorough assessments of essential supplies, developing detailed procurement plans, updating evacuation procedures to address a range of hazard scenarios, and training staff in providing psychosocial support. Structural upgrades and the establishment of mental health programs are also recommended.